ANALISIS PERLINDUNGAN HUKUM TERHADAP KREDITUR SEPARATIS PEMEGANG HAK TANGGUNGAN YANG KEHILANGAN HAK EKSEKUSI DALAM PROSES KEPAILITAN: - Luqyana Khalda Salsabila; Sri Untari Indah Artati (Faculty of Law, Universitas Trisakti, 2023)
The Central Jakarta Commercial Court issued a decision Number 15/Pdt-Lawsuit Lain-Lain/2019/PN.Niaga.Jkt.Pst regarding bankruptcy asset disputes that have a negative impact on PT Maybank Indonesia Tbk., as a separatist creditor holding Dependent Rights (HT). The problems in this writing is in the form of,